HUMANİSTİC VALUE ORİENTATİONS OF STUDENT IDENTİTY AND THE PARADOX OF SELF-ACTUALİZATİON İN HİGHER EDUCATİON INSTİTUTİONS - Nihad, Aliyev; Masuma, Ganbarova; Aysel, Zahidova; Aysu, Gurbanli (Health and Society, 2026)
This article provides a comprehensive examination of the avenues for cultivating humanistic values in higher education institutions. The primary objective of the study was to identify the psychological characteristics and developmental patterns of the emergence of humanistic values among Azerbaijani students. To this end, an empirical study was conducted among a total of 120 students at Azerbaijan State Pedagogical University. The obtained results show that a high level of altruism is not always directly related to a high level of humanistic thinking. However, it is possible to activate latent potential through the strengthening of socially accepted motivations and to utilize it for the development of humanistic values. Based on the research findings, regardless of students’ levels of self-assessment and self-affirmation, their overall attitude toward humanistic values remains high. The formative influence in the development of these values is attributed to the influential characteristics of social values, which hold a leading position in a professional self-affirmation and value system that reflects the holistic qualities of the personality. It was also determined that there is a positive correlation between humanistic qualities, personality traits, and academic achievements. Although this correlation is weak in some cases, it is statistically significant.